Złości, która się więc pokazuje w dziateczkach nie tak winien ojciec jako matka – wpływ matki na wychowanie swych dzieci w polskich drukowanych oracjach pogrzebowych XVII wieku - Kicińska, Urszula (Biuletyn Historii Wychowania, 2013)
Anger which is appearing in children, father isn’t guilty only mother – influence of the mother on raising one’s children in Polish printed funeral orations of the 17th century. In funeral orations, the fact of being a mother was underlined as the major merit of the dead. The number of children to whom she gave birth and whom she raised were mentioned with pride. So the motherhood constituted the main mission of the woman. Not only nursing children, but also forming their character and mind belonged to the responsibilities of women. A good mother, according to preachers, was supposed to be pious, sensible and hard-working. The Old Polish education ideal, in spite of social and material differences, had more than a class character. It concerned mainly girls, because they rarely expressed their opinion about their education and in less detail. It is possible to distinguish two types of educating women. The first one was called “conservative” and was supposed to prepare young girls for their future role of the wife, the mother and the housewife. The second was known as “progressive” as it recognized the equal status of the man and the woman and therefore she could develop intellectually. The daughters of magnates and rich gentry received their education in aristocratic manor houses or at convent schools, whereas poorer girls had to be satisfied with home upbringing. Nevertheless, irrespective of the place in which the girl received her education, she was prepared for her main practical role of the wife, the mother and the housewife.